2010
DOI: 10.3390/s100302386
|View full text |Cite
|
Sign up to set email alerts
|

Stress Sensors and Signal Transducers in Cyanobacteria

Abstract: In living cells, the perception of environmental stress and the subsequent transduction of stress signals are primary events in the acclimation to changes in the environment. Some molecular sensors and transducers of environmental stress cannot be identified by traditional and conventional methods. Based on genomic information, a systematic approach has been applied to the solution of this problem in cyanobacteria, involving mutagenesis of potential sensors and signal transducers in combination with DNA microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 126 publications
(158 reference statements)
0
84
0
1
Order By: Relevance
“…Moreover, transcripts of the alternative sigma factors sigB (sll0306), sigD (sll2012), and sigH (sll0856) were highly induced in D4, irrespective of Ci supply. These transcripts responded to general stress (Los et al, 2010), high-light and redox stress (Imamura et al, 2003), oxidative stress (Li et al, 2004), or heat stress (Huckauf et al, 2000;Tuominen et al, 2003;Singh et al, 2006). Additionally, the expression of slr1738, coding for a peroxide responsive regulator (PerR)/ferric uptake regulation protein (FUR)-type transcriptional regulator of oxidative stress (Li et al, 2004; Garcin et al, Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, transcripts of the alternative sigma factors sigB (sll0306), sigD (sll2012), and sigH (sll0856) were highly induced in D4, irrespective of Ci supply. These transcripts responded to general stress (Los et al, 2010), high-light and redox stress (Imamura et al, 2003), oxidative stress (Li et al, 2004), or heat stress (Huckauf et al, 2000;Tuominen et al, 2003;Singh et al, 2006). Additionally, the expression of slr1738, coding for a peroxide responsive regulator (PerR)/ferric uptake regulation protein (FUR)-type transcriptional regulator of oxidative stress (Li et al, 2004; Garcin et al, Table I.…”
Section: Resultsmentioning
confidence: 99%
“…Their genome has evolved in such a way that they can sense and respond to different environmental stimuli (Los et al, 2010). Due to their photoautotrophic nature, they have also developed an ability to fine-tune their photosynthetic machinery in response to ambient light quality.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrates that ROS levels are correlated with morphological changes during CCA in F. diplosiphon; however, how this signal is translated into morphological changes by regulating cytoskeletal proteins or components of the cytoskeleton to give final morphological changes is still unknown. Notably, cyanobacterial genomes possess several sensor kinases to sense oxidative stress (Los et al, 2010) and it will be interesting to determine whether morphological changes in F. diplosiphon during CCA involve a sensor kinase of oxidative stress that directly affects the integrity of the cytoskeletal proteins to give the spherical morphology under RL.…”
Section: Ros Ros Gl Rlmentioning
confidence: 99%
“…The two-component signal transduction systems, consisting of histidine kinases and the corresponding response regulators, was previously considered as the predominant phosphorylation based signal transduction mechanism in cyanobacteria [62]. However, recently, comprehensive functional analyses have revealed that Ser/Thr/Tyr kinases and phosphatases play vital roles in regulating many critical processes in cyanobacteria, such as stress adaptation, cell differentiation, cell motility, carbon and nitrogen metabolism and photosynthesis [63].…”
Section: Phosphoproteomementioning
confidence: 99%